Mathematics anxiety in undergraduate business studies students - McCullagh, Orla; Ryan, Maria; Fitzmaurice, Olivia (Teaching mathematics and its applications, 2024)
Abstract Performance in mathematics can be attributed to factors other than mathematical ability. A growing body of literature examines the significant impact of mathematics anxiety (MA) on mathematical performance and individuals' choices concerning study and career pathways. However, much of the focus has been on science, technology, engineering and mathematics subjects, renowned for their high mathematical content. This study examines the prevalence, characteristics and influence of MA in undergraduate business studies students. In all aspects of business, there is a strong impetus for the adoption of artificial intelligence, data analytics and machine learning, prompting reform of business studies curricula. Hence, this is a critical juncture at which to examine MA within this cohort. We survey undergraduate business studies students using the Mathematics Anxiety Scale-UK as a measure of participants' MA and examine its relevance in business major selection. Gender emerges as a key differentiating factor in levels of MA and the selection of business majors.